Erector spinae plane block (ESPB): an adjuvant multimodal analgesic in the Combined Mandibulectomy and Neck Dissection (COMMANDO)—a case report - Jadon Ashok; S. Nair Abhijit; Sinha Neelam; K. Shahi Prashant (Ain Shams Journal of Anesthesiology, 2021)
Abstract Background The Combined Mandibulectomy and Neck Dissection (COMMANDO) surgery results in severe postoperative pain and requires multimodal analgesia (MMA) for its management. We speculated that the erector spinae plane block (ESPB) which is the ultrasound (US)-guided regional technique and has been used in various types of surgeries due to its analgesic benefits could be used as an effective analgesic adjunct in COMMANDO surgery. Case presentation We report a case of a 68-year-old female patient who underwent left side COMMANDO surgery for carcinoma cheek. She was given an ultrasound-guided left erector spinae plane block (ESPB) in the preoperative period with catheter insertion at T3 (3rd thoracic vertebral level). Two boluses of local anesthetic were given each with 10 ml 0.25% ropivacaine one before and one after surgery, and then, the infusion was started with a volumetric pump. The ESPB provided effective intraoperative as well as postoperative pain relief without any side effects. Conclusion US-guided ESPB could be used as a potential opioid-sparing multimodal analgesic in head and neck surgeries based on the pain relief provided and the spread of contrast on imaging. This hypothesis needs to be explored in the form of case series and adequately powered randomized controlled trials.